The efficacy of radical radiotherapy and radiochemotherapy in patients with primary inoperable locally advanced rectal cancer - Wydmański, Jerzy; Suwiński, Rafał; Majewski, Wojciech; Mąka, Bogusław; Kim, Larisa (Contemporary Oncology/Współczesna Onkologia, 2005)
Purpose: The purpose of the study is to evaluate the tolerance and efficacy of radical radiotherapy and radiochemotherapy in patients with primarily inoperable rectal cancer. Methods and material: The analysis is based on 20 patients with primarily inoperable rectal cancer. There were 16 men and 4 women aged 22-76 years (median 55 years). Six patients were treated using combined radiochemotherapy (group I). The PTV included rectum and pelvic lymph nodes, the total radiation dose to the PTV ranged from 30 Gy to 45 Gy. Chemotherapy was based on 5-Fu and LV and was concomitantly administered during radiation. Fourteen patients were treated using radical radiotherapy alone (group II). The total radiation dose to the tumor ranged from 60 Gy to 66 Gy and the pelvic lymph nodes were irradiated using the total dose of 42 Gy. In patients treated with radiotherapy alone, conventional (i.e., dose of 1.8-2.0 Gy per fraction) or hyperfractionated (i.e., dose of 1.5 Gy b.i.d. per fraction) regimens were used. Four to six weeks after completion of radiotherapy patients underwent surgical examination to assess tumor resectability. Results: Acute treatment toxicity was assessed using the Dische system and ranged from 0 to 14 points (median 3 points). Skin reaction in 50% of patients and diarrhea in 40% of patients were the most frequent toxicities. Late treatment toxicity was observed in 2 patients (10%). Radiotherapy was interrupted in one patient due to disease progression. Tumor regression was observed in 14 patients (70%) after radiotherapy, which allowed radical resection to be performed. Radical resection was possible in 3 patients (50%) from group I and in 11 patients (79%) from group II. In 6 patients (30%), radical resection was not possible due to local tumor extension. In a group of patients after surgery actuarial 3-year disease-free survival and 3-year overall survival were 58% and 82%, respectively. Conclusions: Radical radiotherapy, either alone or in combination with chemotherapy, in patients with primary inoperable locally advanced rectal cancer is safe and well tolerated. This treatment allowed radical resection to be performed in a substantial percentage of patients and with primarily inoperable rectal cancer. The tolerance of treatment was satisfactory.